Ontdekkingstocht - De Coene, Jozef; Cantré, Jozef; Streuvels, Stijn (Kortrijk : De Eikelaar, 1931)
Bibliotheek Jan Baghus
Bibliotheek Camille Huysmans
Dedicator: De Coene, Jozef, dedicatee: Huysmans, Camille
Genummerd exemplaar, nummer 106
Nederlands
Monografie